POTENSI KERAGAMAN JENIS MANGROVE TEKOLABBUA, KABUPATEN PANGKAJENE DAN KEPULAUAN (Potential Diversity Of Tekolabbua Mangroves, Pangkajene And Kepulauan Regency) - Nirawati, Nirawati; Djafar, Muliana; Hadija, Hadija; athira, Ain (Universitas Tanjungpura, 2024)
Information related to the potential of mangroves in the preservation and breeding of forest ecosystems is not comprehensive enough to support the function of mangrove forest ecosystems at large. This study aims to determine the potential diversity of mangrove species in Tekolabbua district pangkajene and islands. The method used was systematic line sampling with random start and data analysis using quantitative descriptive approach to determine the potential diversity of mangrove species based on the structure, composition, and diversity of mangrove species. The results showed that the structure of mangrove stands in the diameter class was dominated by Avicennia alba species in each diameter class. The composition of mangrove species found were Sonneratia alba, Avicennia alba, and Rhizophora mucronata with INP at the seedling growth rate of Avicennia alba 200% and at the sapling and tree level the highest INP was found in Avicennia alba with an INP value of 105.799% sapling level and 159.97% tree level INP. While the lowest INP value is found in Rhizophora mucronata species with an INP value for the sapling level of 95.54% and an INP value for the tree level of 45.16%. The species diversity index is classified as low with a moderate level of evenness, indicating that the Tekolabbua mangrove community, Pangkajene Regency and the islands are classified as still unstable.Keywords: Stand, Structure, Species, Composition, Mangrove.AbstrakInformasi terkait potensi mangrove dalam pelestarian dan pemuliaan ekosistem hutan belum cukup komprehensifnya dalam medukung fungsi ekosistem hutan mangrove secara luas. Penelitian ini bertujuan untuk mengetahui potensi keragaman jenis Mangrove di Tekolabbua kabupaten pangkajene dan kepulauan. Metode yang digunakan adalah systematic line sampling with random start dan Analisis data mengunakan pendekatan deskriptif kuantitatif untuk mengetahui potensi keragaman jenis mangrove berdasarkan struktur, komposisi, dan keragaman jenis mangrove. Hasil penelitian menunjukkan struktur tegakan mangrove pada kelas diameter didominasi oleh spesies Avicennia alba pada setiap kelas diameter. Komposisi jenis mangrove yang ditemukan adalah Sonneratia alba, Avicennia alba, dan Rhizophora mucronata dengan INP pada laju pertumbuhan semai Avicennia alba 200% dan pada tingkat pancang dan pohon INP tertinggi terdapat pada Avicennia alba dengan nilai INP sebesar tingkat pancang 105,799% dan INP tingkat pohon 159,97%. Sedangkan nilai INP terendah terdapat pada spesies Rhizophora mucronata dengan nilai INP untuk tingkat pancang 95,54% dan nilai INP untuk tingkat pohon 45,16%. Indeks keanekaragaman jenis tergolong rendah dengan tingkat kemerataan sedang, menunjukkan bahwa komunitas mangrove Tekolabbua Kabupaten Pangkajene dan kepulauan tergolong masih labil.Kata kunci: Struktur, Tegakan, Komposisi, Keragaman, Kemerataan, Mangrove